2021
DOI: 10.1128/jvi.00394-21
|View full text |Cite
|
Sign up to set email alerts
|

The Multidrug Efflux System AcrABZ-TolC Is Essential for Infection of Salmonella Typhimurium by the Flagellum-Dependent Bacteriophage Chi

Abstract: Bacteriophages are the most abundant biological entities in the biosphere. Due to their host specificity and ability to kill bacteria rapidly, bacteriophages have many potential healthcare applications, including therapy against antibiotic-resistant bacteria. Infection by flagellotropic bacteriophages requires a properly rotating bacterial flagellar filament. The flagella-dependent phage χ (Chi) infects serovars of the pathogenic enterobacterium Salmonella enterica. However, cell surface receptors and proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 70 publications
0
32
0
1
Order By: Relevance
“… 197 Similarly, in Salmonella Typhimurium, the TolC appears to be essential for the infection by the Chi-phage. 198 Likewise, TolC from V. cholerae is also utilized by the VP3 phage to gain entry into cells. 199 The AcrEF-TolC complex from E. coli has been posited to play a role in the maintenance of normal cell division.…”
Section: Biological Functions Outside Of Multidrug Resistancementioning
confidence: 99%
“… 197 Similarly, in Salmonella Typhimurium, the TolC appears to be essential for the infection by the Chi-phage. 198 Likewise, TolC from V. cholerae is also utilized by the VP3 phage to gain entry into cells. 199 The AcrEF-TolC complex from E. coli has been posited to play a role in the maintenance of normal cell division.…”
Section: Biological Functions Outside Of Multidrug Resistancementioning
confidence: 99%
“…Initial interactions are mediated by phage encoded RBPs. Flagellotropic phages first bind to the bacterial flagellar filament and have been shown to interact with secondary cell surface receptors such as LPS, efflux pumps, and CPS [ 13 , 14 , 40 , 47 ]. RBPs in non-flagellotropic phages have been identified, resulting in a wealth of knowledge surrounding common features of these proteins including resistance to proteolysis, thermostability, and the ability to degrade glycans [ 16 , 20 , 21 , 24 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, phage-host interactions during viral entry are typically investigated unilaterally, largely focusing on the bacterial hosts. Such studies have identified outer membrane proteins, efflux pumps, capsular polysaccharide (CPS), lipopolysaccharide (LPS), pili, and flagella as receptors used by bacteriophages [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Inarguably, a holistic understanding of the mechanisms underlying phage entry entails equally detailed analyses of phage components involved in interacting with bacterial receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption of bacteriophages to the surface of bacteria is usually described by several stages: (1) initial contact, (2) reversible binding, and (3) irreversible attachment [ 128 , 147 ]. Therefore, the question arises about the relationship between receptors (porins, pumps, channels) and the ability of bacteriophage nucleic acids to penetrate into cells [ 148 ]. Whether bacteriophages use the structural features of receptors for penetration through the outer membrane or only for recognition and attachment to the surface of bacteria remains debatable.…”
Section: Mdr Pumps As Phage Receptorsmentioning
confidence: 99%